Recalling Critical Incidents for Professional Learning - Poudel, Guru (Journal of NELTA Gandaki, 2019)
Teachers have to identify their own potentials and problems in order to look their way forward. In their ongoing process of teaching and learning, teachers might have encountered many critical incidents. Recalling critical incidents has worth in restructuring the pedagogical approaches and reshaping the classroom activities because teachers develop themselves if there is challenge and responsibility. Having such a claim in mind set, this article aims to unpack the Nepalese ESL lectures stories of critical incidents and to examine the role of recalling critical incidents for their professional learning. It has been developed on the basis of the narrative of three EFL lecturers. After the thematic analysis of the data obtained through in-depth interview, it has been found that EFL lectures had a story of unplanned and unexpected event of the classroom and they recalled such stories as a part of professional learning. Similarly, the reflection of critical events gave them some kind of relief in teaching practices and the events taught them a number of strategies like persuasive or threatening, co-operating, caring and sometimes being indifferent to the students.